ALIRAN-ALIRAN PEMIKIRAN ALTERNATIF DALAM AKUNTANSI - Nur Indriantoro (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
This paper discusses the school of thinking within the accounting circle otherthan structural functionalism which is the mainstream. The other alternative schoolsdiscussed that influenced the accounting development are interpretivism, radicalstructuralism, radical humanism, and postmodernism.